2019
DOI: 10.1042/bsr20181987
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of IL-17 and NF-κB gene polymorphisms with susceptibility and prognosis in acute respiratory distress syndrome in a chinese population

Abstract: The present study was performed to investigate the association between interleukin-17 (IL-17) and nuclear factor κB (NF-κB) gene polymorphisms and the risk and prognosis of acute respiratory distress syndrome (ARDS) in a Chinese population. A total of 210 Chinese patients with ARDS were selected as the study group, 210 individuals who were identified as at-risk patients but did not meet criteria for ARDS were recruited as the control group. Three single nucleotide polymorphisms (SNPs) of IL-17, including rs763… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 23 publications
2
35
1
Order By: Relevance
“…Therefore, the NF-κB1 gene is one of the key genes in the NF-κB signalling pathway. There have been many studies on the association of genetic polymorphisms of the NF-κB1 gene with immune-related diseases such as inflammatory bowel disease[24], infectious diseases[25] and tumours[17, 23, 26]. There is evidence that NF-κB1 may directly interact with the DNA-binding domain of PXR to suppress its expression and inhibit its transactivation[27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the NF-κB1 gene is one of the key genes in the NF-κB signalling pathway. There have been many studies on the association of genetic polymorphisms of the NF-κB1 gene with immune-related diseases such as inflammatory bowel disease[24], infectious diseases[25] and tumours[17, 23, 26]. There is evidence that NF-κB1 may directly interact with the DNA-binding domain of PXR to suppress its expression and inhibit its transactivation[27].…”
Section: Introductionmentioning
confidence: 99%
“…The release of many cytokine and the regulation of inflammatory pathways are regulated by some transcription factors such as NF-κB, thus, any changes in their structure and expression might influence cytokine production and ARDS progress [61]. Since increased IL-17 may serve as a biomarker to indicate the severity of ARDS in patients with sepsis-induced ARDS [62], researchers have estimated the IL-17 (rs763780, rs2275913, and rs8193036) and NF-κB1 (rs3774934) polymorphisms in a Chinese population that were associated with ARDS prediction and prognosis [63]. This conclusion further shows that the detection of related gene expression and variants has an important role in the prediction and prevention of the occurrence and development of ARDS.…”
Section: Resultsmentioning
confidence: 99%
“…63,64 A retrospective analysis of IL-17 gene polymorphisms in patients with acute respiratory distress syndrome (ARDS) revealed that patients with a polymorphism that resulted in attenuated IL-17 production had an increased 30-day survival, whereas a genetic polymorphism that resulted in producing more IL-17 correlated with decreased survival. 65 Mikacenic et al measured circulating IL-17A in ARDS and showed that elevated circulating and alveolar levels of IL-17A are associated with increased percentage of alveolar neutrophils, alveolar permeability and organ dysfunction in ARDS. 66 However, there is no detailed information about the association between frequency of polymorphisms of IL-17A and IL-17F genes of COVID patients among the populations.…”
Section: Discussionmentioning
confidence: 99%